The Breaking and Mending of meso-Tetraarylporphyrins: Transmuting the Pyrrolic Building Blocks - Brückner, Christian (Accounts of chemical research, 2016)
Naturally occurring porphyrins and hydroporphyrins vary with respect to their ring substituents and oxidation states, but their tetrapyrrolic frameworks remain fully preserved across all kingdoms of life; there are no naturally occurring porphyrin-like macrocycles known that contain nonpyrrolic building blocks. However, the study of porphyrin analogues in which one or two pyrroles were replaced with nonpyrrolic building blocks might shed light on the correlation between structural modulation and ground and excited state optical properties of the “pigments of life”, unlocking their mechanisms of function. Also, porphyrinoids with strong absorbance and emission spectra in the NIR are sought after in technical (e.g., light-harvesting) and biomedical (e.g., imaging and photochemotherapy) applications. These porphyrin analogues, the so-called pyrrole-modified porphyrins (PMPs), are synthetically accessible using total syntheses. Alternativelyand most handilythey can also be formed by conversion of synthetic porphyrins. Guided by older reports of the fortuitous modifications of porphyrins into PMPs, our research program generalized the so-dubbed “Breaking and Mending of Porphyrins” approach toward PMPs. This method to convert a pyrrole in meso-tetraarylporphyrins to a nonpyrrolic building block with high precision relies on a number of distinct steps. Step 1: The porphyrin is functionalized in a way that activates one or two peripheral double bonds toward breakage; in all cases surveyed here, this step is an osmium tetroxide-mediated dihydroxylation to generate dihydroxychlorin and tetrahydroxybacteriochlorins. Step 2: The activated, dihydroxylated β,β′-bond is “broken”. Step 3: The functional groups resulting from the ring-cleavage reactions are utilized in subsequent “mending” steps to form the PMPs, that themselves may be subject to further modifications, Step 4. Thus, PMPs in which a pyrrole was degraded to an imine linkage, contracted to a four-membered ring, or expanded by oxygen, sulfur, carbon, or nitrogen atoms to form six-membered building blocks have become accessible. This approach also allowed the replacement of a single β-carbon atom by a nitrogen or oxygen atom. Depending on the ring size, conformation, conformational flexibility, the oxidation state of the pyrrole replacements, or the presence of substituents that π-extend the chromophores, the PMPs possess porphyrin- or hydroporphyrin-like optical spectra, or they show altogether unique electronic properties. Some PMP classes allow the fine-tuning of their absorption range; others exhibit panchromatic absorption spectra from the UV to the NIR. Several PMPs take up persistent chiral helimeric conformations that could be resolved. This Account summarizes the scopes of the “Breaking and Mending” methodology with a special focus on laying out the structural diversity of PMPs accessible from meso-tetraarylporphyrins and highlighting their optical properties, with the aim of encouraging their further study and application.